Методика передачи данных через порт USB в микроконтроллерах на базе ядра Cortex M4 в системах измерения и управления на транспорте - Сериков, Сергей Анатольевич; Борисенко, Анатолий Николаевич; Богаевский, Александр Борисович; Вовк, Е. Г. (НТУ "ХПИ", 2014)
В статье анализируются аппаратные возможности передачи данных через порт USB современных микропроцессорных систем на базе ядра Cortex M4 и предлагается методика разработки измерительных систем с возможностью передачи данных к персональным или специализированным измерительным комплексам.

The article analyses the use of measuring and computing power of modern microcontrollers based on the Cortex M4 core in the organization of control systems of transport means and development methodology object software for hardware USB2.0 data interface in a software development environ-ment Сoocox Coide. These methodological recommendations aimed at familiarization with the working modes of functioning and implementation of the integrated data interface USB microcontrollers compa-ny STMicroelectronics, as well as represented company-developer of the standard library files and examples organization of information transfer between the microcontroller and a personal computer. This article was published on the basis of received practical results of the organization of communica-tion between the microcontroller and the various subsystems in the information management system of the vehicle.
Data transmission technique through USB port in microcontrollers on the basis of COR-TEX M4 kernel in measurement and management systems on transport
Keywords: микропроцессорная техника; транспортное машиностроение; микропроцессор; передача данных; microprocessor; transport mechanical engineering; microcontroller; CORTEX; data transmission